Structural analyses for 3d prefabricated module with an innovative ultra-thin steel base at various stages of modularisation. (1st April 2022) - Wasim, Muhammad; Van Le, Tu; Oliveira, Osmar; Kieu, Son; Ngo, Tuan Duc
Abstract: Modularisation of efficient and cost-effective volumetric modules is a complicated procedure that involves adept material knowledge, advanced structural analyses skills and sound manufacturing awareness for professionals involved in it. This paper presents the design and structural modelling of an efficient and highly optimised module having an ultrathin mild steel base. First, the structural analysis, and then the testing of the manufactured ultrathin base of the module was performed. Then, the structural analyses for the deflections of the entire prefabricated module using computer-aided Extended Three-Dimensional Analysis for Building System (ETABS) were carried out. The modal analysis for the module was also performed to observe and develop connection strategies against the lateral deformations. Angle brackets connections were proposed at the corner of the adjacent walls in their top, middle and bottom to control lateral deformations that can induce damages to the non-structural elements. Moreover, a lifting system for the safe transport of the module was designed. Furthermore, the analysis revealed that the serviceability of the module onsite was enhanced by providing packers support at the critical locations of the base of the module. The findings of this paper are significant and provide the framework with full guidance for optimised, cost-effective and safe design, and installation of the volumetric modules for modular building projects. Highlights: An ultra-thin base of the 3D module was manufactured and tested. The structural capacity of the base is enhanced by CFC sheets and steel beams. Analyses were carried out at all stages of modularisation. The serviceability issues of the base were tackled by providing plastic packers support. A lifting assembly and framework for transportation of a 3D module were proposed.